Effectiveness of Revenue Revenue from Solid Waste Services in Bandar Lampung City - Emilia, Mutiara; Ratih Y.T, Arivina (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to find out the effectiveness and potential of receiving waste levies in the city of Bandar Lampung. This research uses secondary data collection techniques, namely data collection techniques carried out by collecting historical data or documents that are relevant to this research. The data used are the target for receiving waste levies, the actual receipt of waste levies, the number of households in Bandar Lampung City and the waste levy rates. The research results show that every year the effectiveness of the waste levy does not reach the target and analysis of potential levy revenue shows an increase.